Expression of tert Prevents ALT in Zebrafish Brain Tumors - Idilli, Aurora Irene; Cusanelli, Emilio; Pagani, Francesca; Berardinelli, Francesco; Bernabé, Manuel; Cayuela, María Luisa; Poliani, Pietro Luigi; Mione, Maria Caterina (Frontiers in Cell and Developmental Biology, 2020)
The activation of a telomere maintenance mechanism (TMM) is an essential step in cancer progression to escape replicative senescence and apoptosis. Alternative lengthening of telomeres (ALT) is found in a subset of malignant brain tumors with poor outcomes. Here, we describe a model of juvenile zebrafish brain tumor that progressively develops ALT. We discovered that reduced expression of tert, linked to a widespread hypomethylation of the tert promoter and increase in Terra expression precedes ALT development. Surprisingly, expression of tert during juvenile brain tumor development led to reduced proliferation of tumor cells and prolonged survival. Most importantly, expression of tert reverted all ALT features and normalizes TERRA expression, promoted heterochromatin formation at telomeres, and attenuated telomeric DNA damage. These data suggest that the activity of telomerase goes beyond telomere maintenance and has profound consequences on genome stability.